Assessing universal competencies of students of non-linguistic specialties - Yulia B. Drobotenko; Natalia A. Nazarova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The rapidly developing labor reality requires a modern specialist to be ready for rapid adaptation in the professional space, mobility within the labor market and constant self-improvement. The training of such specialists at the university aims at the formation of both highly professional and flexible (universal) competencies that provide the ability to think systematically, critically assess problem situations and search for a variety of resources for solving professional problems. Universal competencies are represented by eight groups which suppose that University training in its basic part should be identical at all university levels of education and for all areas and specialties. And it is grounded on the principles of universalism. The purpose of the paper is to present the concept of universal competencies in a meaningful and structural way and to determine the possibilities of the case-testing method in their evaluation. The research methodology is based on the principles of flexibility and variability applied to research process organization, practice-oriented principles of the results of research procedures. It is focused on a holistic, reflexive-analytical and methodological-instructive presentation of the results of diagnostics that reflect the development of universal competencies.